Manganese‐Catalyzed Selective Oxidation of Aliphatic CH groups and Secondary Alcohols to Ketones with Hydrogen Peroxide. Issue 9 (5th September 2013) - Dong, Jia Jia; Unjaroen, Duenpen; Mecozzi, Francesco; Harvey, Emma C.; Saisaha, Pattama; Pijper, Dirk; de Boer, Johannes W.; Alsters, Paul; Feringa, Ben L.; Browne, Wesley R.
Abstract An efficient and simple method for selective oxidation of secondary alcohols and oxidation of alkanes to ketones is reported. An in situ prepared catalyst is employed based on manganese(II) salts, pyridine‐2‐carboxylic acid, and butanedione, which provides good‐to‐excellent conversions and yields with high turnover numbers (up to 10 000) with H2O2 as oxidant at ambient temperatures. In substrates bearing multiple alcohol groups, secondary alcohols are converted to ketones selectively and, in general, benzyl CH oxidation proceeds in preference to aliphatic CH oxidation.